STUDENT PERCEPTIONS OF LMS AT THE FACULTY OF ENGINEERING TRUNOJOYO UNIVERSITY MADURA - Kurniawa Eka Permana; Mochammad Kautsar Sophan; Arif Muntasa (Universitas Trunojoyo Madura, 2022)
This study aims to determine student perceptions of the Learning Management System (LMS) during the Corona pandemic. Currently, many educational institutions are conducting online learning and using LMS in their activities. The LMS system is used as a medium for managing the learning process. By utilizing the LMS, schools can register, identify lesson plans, monitor learning, and evaluate learning. During the pandemic learning period, LMS plays a very important role in determining the success of learning targets. It is therefore important to get students' perceptions of the LMS used. The LMS system used in this study is a free web-based LMS system and can be used by the public. The assessment methodology used to fulfill the research objectives uses a Likert-type scale. This study provides insight into the LMS preferred by students. The results of this study can be used as a reference in the selection of the LMS tool used. The method we use is a simple questionnaire using a google form. This research is included in quantitative research. From the results of the research, it is evident that there are two things that are of great concern to students, namely the LMS is easy to use and is able to facilitate the availability of teaching materials. Respectively with a total agree of 86.8% and 93.3%.